Passive-Aggressive Trading: The Supply and Demand of Liquidity by Mutual Funds. (9th February 2022) - Christoffersen, Susan K; Keim, Donald B; Musto, David K; Rzeźnik, Aleksandra
Abstract: Active mutual funds supply liquidity when demanding it becomes uneconomical. They tilt toward cheaper buy trades after inflows deplete their trading ideas, when trading ideas in general run low, and when they have more stocks to supply liquidity to, and their cheaper trades perform worse. Their largest trades are more likely to supply liquidity, explaining why they were not broken up. Funds perform better when they pay more for their buys and perform worse when they pay more for their sells, consistent with the implied value of the trades and the correlation between what a fund trades and what it holds.